Nanobody-based recombinant antivenom for cobra, mamba and rinkhals bites - Shirin Ahmadi; Nick J. Burlet; Melisa Benard-Valle; Alid Guadarrama-Martínez; Samuel Kerwin; Iara A. Cardoso; Amy E. Marriott; Rebecca J. Edge; Edouard Crittenden; Edgar Neri-Castro; Monica L. Fernández-Quintero; Giang T. T. Nguyen; et al. (Nature, 2025)
Abstract Each year, snakebite envenoming claims thousands of lives and causes severe injury to victims across sub-Saharan Africa, many of whom depend on antivenoms derived from animal plasma as their sole treatment option 1 . Traditional antivenoms are expensive, can cause adverse immunological reactions, offer limited efficacy against local tissue damage and are often ineffective against all medically relevant snake species 2 . There is thus an urgent unmet medical need for innovation in snakebite envenoming therapy. However, developing broad-spectrum treatments is highly challenging owing to the vast diversity of venomous snakes and the complex and variable composition of their venoms 3 . Here we addressed this challenge by immunizing an alpaca and a llama with the venoms of 18 different snakes, including mambas, cobras and a rinkhals, constructing phage display libraries, and identifying high-affinity broadly neutralizing nanobodies. We combined eight of these nanobodies into a defined oligoclonal mixture, resulting in an experimental polyvalent recombinant antivenom that was capable of neutralizing seven toxin families or subfamilies. This antivenom effectively prevented venom-induced lethality in vivo across 17 African elapid snake species and markedly reduced venom-induced dermonecrosis for all tested cytotoxic venoms. The recombinant antivenom performed better than a currently used plasma-derived antivenom and therefore shows considerable promise for comprehensive, continent-wide protection against snakebites by all medically relevant African elapids.